Isotherms and isosteric heat of sorption of two varieties of Peruvian quinoa - Pumacahua-Ramos, Augusto (2016)
The isosteric heats of sorption of two varieties of quinoa (Chenopodium quinoa Willd.) grain were determined by the static gravimetric method at four temperatures (40, 50, 60 and 70 °C) and in relative humidity environments provided by six saturated salt solutions. Six mathematical equations were used to model the experimental data: GAB, Oswin, Henderson, Peleg, Smith and Halsey. The isosteric heat of sorption was determined using the parameters of the GAB model. All the equations were shown to be appropriate by the coefficients of determination (R2) and the mean absolute error (MA%E). The influence of temperature was observed because the adsorption of water by the grains was lower at higher temperatures. The equilibrium moisture contents for security of storage, for long periods of time at water activity lower than 0.65, were 12 - 13%. The effect of temperature on the parameters of the GAB model was analysed using the exponential Arrhenius equation. The isosteric heats of sorption were determined by applying the Clausius-Clapeyron equation as a function of humidity. The isosteric heat at 5% moisture for grains of the Blanca de Juli variety was 3663 kJ/kg and for the Pasankalla variety it was 3393 kJ/kg. The experimental data for isosteric heat as a function of humidity were satisfactorily modelled using three mathematical equations.